PELATIHAN PENDIDIKAN KESEHATAN GIGI PADA GURU-GURU DENGAN MEMAKAI MEDIA VIDEO TUTORIAL MENYIKAT GIGI DI MADRASAH IBTIDAIYAH - Nining Ningrum; Deru Marah Laut; Yonan Heriyanto (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2022)
Community behavior is strongly influenced by knowledge of dental health which is still low so that public awareness of the importance of maintaining and maintaining dental and oral health is also low. Riskesdas 2018 data, only 2.8% of the Indonesian population aged more than 3 years who have brushed their teeth properly, brushing 2 times a day in the morning after eating and at night before going to bed. Health education through video media has advantages in terms of providing good visualization so as to facilitate the process of absorbing knowledge. The implementation method includes several activities, namely: providing dental and oral health training for Islamic Islamic Boarding School Madrasah teachers no. 13, carrying out mentoring when trained teachers carry out "knowledge transfer" to students, carrying out mentoring when teachers provide material counseling dental health for their students, providing assistance when teachers develop a mass toothbrushing program using video tutorials on brushing teeth and scheduled counseling for students and carrying out evaluations. Results of Dental Health Training for 10 partner teachers-1 and 10 partner teachers-2 selected accompanied by cognitive evaluation in the form of pre-posttest and evaluation of brushing skills; Toothbrush guidance along with video screening of Toothbrushing Tutorials for Ibtidaiyah and Madrasah Diniyah students. The results of the training for teachers from both Madrasahs are quite good where there is an increase in the average achievement of pre and posttest scores.